Chronic disease prevention programs offered by Aboriginal Community Controlled Health Services in New South Wales, Australia. (9th February 2021) - Sinka, Victoria; Lopez‐Vargas, Pamela; Tong, Allison; Dickson, Michelle; Kerr, Marianne; Sheerin, Noella; Blazek, Katrina; Teixeira‐Pinto, Armando; Stephens, Jacqueline H.; Craig, Jonathan C.
Abstract: Objectives : To identify and describe chronic disease prevention programs offered by Aboriginal Community Controlled Health Services (ACCHSs) in New South Wales (NSW), Australia. Methods : ACCHSs were identified through the Aboriginal Health and Medical Research Council of NSW website. Chronic disease programs were identified from the Facebook page and website of each ACCHS. Characteristics, including regions, target population, condition, health behaviour, modality and program frequency were extracted and summarised. Results : We identified 128 chronic disease programs across 32 ACCHSs. Of these, 87 (68%) programs were broad in their scope, 20 (16%) targeted youth, three (2%) targeted Elders, 16 (12%) were for females only and five (4%) were for males only. Interventions included physical activity (77, 60%), diet and nutrition (74, 58%), smoking (70, 55%), and the Aboriginal and Torres Strait Islander Health Check (44, 34%), with 93 programs (73%) of ongoing duration. Conclusions : Chronic disease prevention programs address chronic conditions by promoting physical activity, diet and nutrition, smoking cessation and health screening. Most target the general Aboriginal community, a few target specific groups based on gender and age, and more than one‐quarter are time‐limited. Implications for public health : Chronic disease programs that are co‐produced with specific groups, based on age and gender, may be needed.